The Influence of Bat Guano on Peat Soil Properties in the Oil Palm Plantations - Farah Bafadhal; Ahmad Fauzi; Diana Nurani; Dicky Adihayyu Monconegoro (UNIVERSITY OF LAMPUNG, 2023)
Highlighting the role of bat guano as an organic fertilizer housing beneficial microbes for soil and plants. The research aimed to assess the effect of bat guano on bacterial diversity and chemical and nutrient properties of peat soil in the vicinity of a bat cave within oil palm plantation in West Sulawesi, Indonesia. Four samples, namely bat guano (BG), peat soil (PS), peat soil mixed with bat guano (PSM), and peat soil inside the cave (PSI) were assessed. Organic carbon, pH, total nitrogen, the C/N ratio, Cation Exchange Capacity (CEC), Base Saturation (BS), macronutrients, and micronutrients were measured across all samples. Bacteria from the samples were also isolated, and their capability in hydrolyzing urea, solubilizing phosphate, solubilizing potassium, and producing the Indole Acetic Acid (IAA) hormone was characterized. The influence of bat guano was found on the enhancement production of IAA hormone, pH, organic carbon, total nitrogen, C/N ratio, CEC, BS, macronutrients, and micronutrients. The results also demonstrated substantial bacterial community resemblance between PSM and BG in contrast to the original PS (3:1). Meanwhile, peat soil inside the cave was indicated unique and has bacterial diversity, which can hydrolyze urea, solubilizing phosphate, and potassium.